Risk factors associated with occupational stress among Malaysian construction professionals - Nur Syafiqah, Fauzan; Nur Alia Farahanin, Mohd Tajuddin; Neroshini, Thanarajee; Dayana Hazwani, Mohd Suadi Nata; Ezrin Hani, Sukadarin; Widia, Mirta (Universitas Indonesia, 2023)
Background: Construction industries that focus on project-based nature, pressure, and long hours may lead to job-related stress among workers. In many emerging nations, robust economic growth plans generate occupational depression, anxiety, and stress among construction industry personnel. This study aims to determine the relationship between these items and the risk factors (demographic) among Malaysian construction professionals. Methods: A cross-sectional study was carried out among 173 Malaysian construction professionals. A DASS-21 questionnaire is used to survey eligible respondents. Results: Findings show that construction professionals have a high level of stress (54.9%), anxiety (48.5%), and depression (37%). Gender is significantly associated with stress (p = 0.000) and depression (p = 0.000). In turn, stress (p = 0.038), anxiety (p = 0.000), and depression (p = 0.001) all demonstrate a significant relationship with health status Conclusions: Health status is the risk factor most significantly associated with occupational stress. Given the findings, construction managers can help protect their employees and their mental health by promoting a healthy workplace through stress management and social activities.